2023
DOI: 10.5267/j.ijdns.2022.9.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reliable data transfer and efficient computer network features in Jordanian banks accounting information systems performance based on hardware and software, database and number of hosts

Abstract: Reliable data transfer protocols are algorithmic techniques that guarantee the safe and secure transport of data through networks that could experience data loss or corruption. The performance of the systems and some accounting information systems (AIS) will be negatively impacted if the real-time data is not sent. The main factors that affect the performance of computer networks are the number of users, the hardware and software and the bandwidth. The computer network performance will play a role in the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, the results indicated that OC partially mediates the relationship between IA and AIS in Jordanian banks. This result agreed with the results of the results of Jarah et al 2023a;Putra 2023;Irfan and Hamimi 2023;Amira and Permatasari 2022;Wahyuni et al 2022;Alawaqleh 2021;Yusuf and Kanji 2020;Mulyani et al 2019;Pura 2017;and Ömer 2016, whose results indicated that AIS and IA had a significant influence on internal control, and the findings also revealed that the AIS and IA had a favorable and substantial influence on internal control at the same time. As the results of Rachman and Fitri (2023) indicated, operational auditing and AIS have a considerable impact on sales performance, and internal control has no bearing on sales performance.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the results indicated that OC partially mediates the relationship between IA and AIS in Jordanian banks. This result agreed with the results of the results of Jarah et al 2023a;Putra 2023;Irfan and Hamimi 2023;Amira and Permatasari 2022;Wahyuni et al 2022;Alawaqleh 2021;Yusuf and Kanji 2020;Mulyani et al 2019;Pura 2017;and Ömer 2016, whose results indicated that AIS and IA had a significant influence on internal control, and the findings also revealed that the AIS and IA had a favorable and substantial influence on internal control at the same time. As the results of Rachman and Fitri (2023) indicated, operational auditing and AIS have a considerable impact on sales performance, and internal control has no bearing on sales performance.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, with audits features in the accounting system, many frauds, irregularities, and mistakes may be avoided or monitored and addressed, where accounting information developments result in the development of information demands for interested parties as well as the necessity for quality procedures and performance in creating information (Wahyuni et al 2022). In a study by Jarah et al (2023a), it was proven that the IA has an effect on the relationship between the AIS and the performance of Jordanian banks. Wahyuni et al (2022) findings revealed that the AIS and IA had a partially good and substantial influence on internal control.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology sometimes advances unexpectedly quickly, and across the globe we are seeing great innovations in the area of financial accounting technology. Banks have been forced to innovate as a result of the disruption that financial accounting technology is causing to the fundamental financial services they provide (Jarah, Jarrah, Almomani, AlJarrah, & Al-Rashdan, 2023). Customers may have easier access to superior services as a result, and the regulatory bodies now face greater risks as a result of these developments.…”
Section: Introductionmentioning
confidence: 99%